Partial Postero-Medial Superficial Release of the Proximal Crural Fascia in Patients with Positive Silfverskiold's Test: Case Series of Clinical Outcomes and Novel Technique. Issue 4 (November 2022) - Mattos, Ivan; Azam, Mohammad T.; Ubillus, Hugo A.; Weiss, Matthew B.; Kennedy, John G.
Category: Ankle; Hindfoot; Lesser Toes; Midfoot/Forefoot Introduction/Purpose: Ankle limitation to dorsiflexion in an extended knee is observed during the second rocker of gait in patients with positive Silfverskiold test confirming an isolated gastrocnemius contracture (IGC). Tendons and muscles share intrinsic contractility and relaxation properties which can be modified during physiotherapy in comparison to the fascia which lacks it. The present study describes a case series of patients with positive Silfverskiold associated with various foot pathologies who underwent a selective fasciotomy of the postero-medial superficial portion of the crural fascia. The purpose of this study is to describe the surgical technique and clinical outcomes of this procedure. We hypothesize that this procedure can reach satisfactory clinical outcomes with the advantage of being a less invasive procedure. Methods: 26 patients treated with partial postero-medial superficial release (PMSR) of the crural fascia from January to October 2021 for IGC with associated chronic foot pain were included. Inclusion criteria considered patients with diagnosis of foot pain with IGC and positive Silfverskiold test. A transverse incision was made 2 cm distal to the flexion crease starting at the intermuscular line of the gastrocnemius muscle, 4 cm medially (Figure 1). Subcutaneous dissection was performed identifying the neurovascular bundle. A horizontal incision was performed to the superficial posterior fascia of the medial gastrocnemius head. The medial gastrocnemius muscle was not sectioned. Patients completed the FADI score previous to surgery and at final follow- up. Data was analyzed using SPSS 20. Paired samples T-tests were performed to identify significance of the difference in pain and function preoperatively and postoperatively with statistical significance set at p<0.05. Descriptive statistics were used for demographic variables. Results: 18 patients underwent partial PMSR of the crural fascia while 8 patients had additional procedures. Mean age of the included patients was 40.6 +/-18.5 years. Specifically, this included 4 feet with a diagnosis of metatarsalgia, 3 feet with metatarsalgia and plantar fasciitis, 6 feet with metatarsalgia, plantar fasciitis and cavus foot, 5 feet with plantar fasciitis, 3 feet with plantar fasciitis and insertional achilles tendinopathy, 4 patients with non-insertional achilles tendinopathy and 1 foot with flexor hallucis longus tendinopathy.The average ankle dorsiflexion increased significantly (p<0.0001) from -1.15 +/-2.15 degrees preoperatively to 10.65+/-2.02 degrees post-operatively. The average FADI score significantly increased (p<0.0001) from 47.54 +/-12.26 preoperatively to 80.46 +/-14.04 post-operatively. The average follow-up was 9.38 +/-3.76 weeks. All patients had a negative Silfverskiold test at final follow-up. Conclusion: Partial postero-medial superficial release (PMSR) of the crural fascia was found to be an effective outpatient procedure when used to relieve foot pain in those patients with an isolated gastrocnemius contracture. Patients who have failed conservative treatment can expect notable improvement with satisfactory FADI scores after the procedure. Future prospective studies should involve a larger number of patients with no additional procedures to be compared with gastrocnemius muscle release procedure for isolated gastrocnemius contracture with associated foot pain.